Dynamic analysis of composite columns in Inelastic state - Rezaie Hajidehi, Mohsen; Darvizeh, Abolfazl; Mohammad Ranjbar, Malek (International Journal of Engineering and Technology, 2013)
The main objective of this study is analyzing Seismic behavior of composite columns in frame in inelastic state under dynamic load. Therefore, three type of composite column have been used in this paper. IPB Steel section embedded in concrete (type 1), Concrete-filled thin-walled steel sections (type 2), half concreted IPB sections (type 3) which are designed for 3 and 8 floor frame tenement in plastic way. Three earthquake accelerogram have been used for analyzing model seismic behavior and model analysis has been done in non-linear dynamic analysis with Seismostruct application. The results demonstrated that frame designed by composite columns type 1 and 3 in the flexural behavior, have similar construction behavior in the way that plasticity, softness and good function to dispose lateral forces are the same.  Although Type 2 composite model have large sections, have poor performance in tolerating flexural moment. This event refers to poor role of concrete in tension. On the other hand, the amount of concrete is important in Withstand compressive forces and in constructions with high compressive forces, type 1 and 2 have better performance.